Iddah dalam Mazhab Fiqih dan Perundangan Indonesia - Ahmad Zamzam Saefi (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2023)
After a divorce occurs, a woman cannot immediately marry a man she considers capable of replacing her husband. There are different waiting periods for divorce cases based on the female subject. This waiting period is known as 'iddah in Islam. In its development, there are differences of opinion among scholars regarding the periods of 'iddah. Each school of thought has its own views and provisions regarding the duration of the iddah, the conditions that terminate iddah, and the rights and obligations of women during the iddah period. This research is a qualitative research with a library research approach. This article discusses these differences, as well as the arguments and legal basis which are the basis for each school of thought in determining the length of 'iddah. We will explore the theological and legal perspectives that shape the views of each school. From the research it was found that in general the iddah according to the 4 Schools of Fikh is almost the same, a sharp difference is in the iddah of divorce for women who are still menstruating and not pregnant, which is based on differences in the meaning of the word qur'u.